Secretor and non-secretor human milk oligosaccharides differentially modulate immune response in the presence of cow’s milk allergen β-lactoglobulin in an in vitro sensitization model - Hellinga, Anneke H.; Zuurveld, Marit; Mank, Marko; Kraneveld, Aletta D.; Garssen, Johan; Spann, Kennedy; Bode, Lars; Willemsen, Linette E. M.; van’t Land, Belinda (Frontiers in Immunology, 2025)
IntroductionFood allergies, like cow’s milk allergy, significantly impact children, with sensitization often beginning during the first year of life. Human milk oligosaccharides (HMOs) may influence this process, as specific HMOs differentially affect mucosal immune responses in vitro. Given the distinct HMO profiles of secretor (Se+) and non-secretor (Se-) milk, we investigate how the full HMO profiles from Se+ and Se- milk affect immune responses in the absence or presence of a cow’s milk allergen.MethodsMonocyte-derived dendritic cells (moDCs) were exposed to isolated Se+ and Se- pooled HMOs (pHMOs), and subsequently co-cultured with naïve T cells to confirm immune modulation. We compared the type 2-activation capability of several cow’s milk proteins via direct exposure to moDCs or via intestinal epithelial cells (IECs) co-cultured with moDCs. Finally, we studied the effect of pHMOs in the presence of cow’s milk allergen β-lactoglobulin (BLG) (via (IECs)) on moDCs and subsequent T cell response.ResultsBoth Se+ and Se- pHMOs dose-dependently activated moDCs, indicated by increased IL8 release and %CD80+ moDCs. Se+ pHMOs tended to increase type 2-associated markers, while also increasing regulatory IL10 release. Se+ pHMOs-pre-exposed moDCs instructed T cells to produce type 2 cytokines like IL13. Se- pHMOs reduced the %CD86+ moDCs but did not drive a type 2 signature in T cells. In the presence of BLG, Se+ pHMOs-pre-exposed moDCs also instructed IL13 release by T cells, while increasing the percentage regulatory T cells. In contrast, co-exposure of BLG with Se- pHMOs only slightly affected moDC phenotype, and these moDCs did not modify T cell phenotypes.ConclusionsSe+ and Se- pHMOs with BLG differentially affected moDC activation. Se+ pHMO-pre-exposed moDCs induced a type 2- and regulatory-associated T cell phenotype. These data suggest that depending on the secretor status, HMOs differentially modulate immune responsiveness in vitro.